Cultivation under different nets and shading levels affect the biomass production, content, yield and chemical composition of Mentha arvensis L. essential oil (Research, Society and Development, 2022)
Mentha arvensis L. is a medicinal and aromatic plant, popularly known as Japanese mint, vick or simply mint. The leaves are used for therapeutic purposes such as stomach problems and vomiting. Essential oil is rich in menthol, used in oral hygiene products, flavorings, food and beverage flavorings, in perfumery and pharmaceutical products. The aim of this work was to evaluate the biomass production, essential oil content and yield of Mentha arvensis L. plants, cultured under thermo-reflective and black screens with different shading levels. The experiment used plants cultured under two kinds of nets (Aluminet and black) with three shading levels (30, 50 and 70%) and (control) under full sunlight. The pots were randomized complete block design in a factorial scheme of 2 x 4, five replications and each plot were four pots (one plant per pot), 20 pots per treatment. It was evaluated the biomass production, essential oil content, yield and chemical composition. The type of shading nets did not influence the growth, essential oil content, yield and chemical composition of Mentha arvensis plants. Shading promoted by nets did not enhancement biomass production, essential oil content and yield. The menthol content increased with increasing shading. Thus, the intercropping of Japanese mint is only recommended with species of the same size. Cultivation with species that can cause shading can affect plant development, essential oil content and yield.